2021
DOI: 10.1021/acscatal.1c00778
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Charge in a Ni(II) Polymerization Catalyst

Abstract: A direct comparison between neutral active sites and their corresponding cationic analogues is enabled by protonation of neutral bis(imino)phenoxy complexes, active for ethylene polymerization. The additional imine motif compared to parent salicylaldiminato catalysts does not influence the microstructure of the products in ethylene polymerization, but allows for the incorporation of a proton right next to the active center in an N•••H + •••O bridge yielding cationic complexes. These show an increased Ni−O bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Note that single-site homogeneous olefin polymerization catalysis usually produces characteristic narrow molecular weight distributions with Đ ∼ 2.0. In some scenarios, broadened polyolefin Đs and multimodality can positively alter melt processing and polyolefin properties. …”
Section: Resultsmentioning
confidence: 99%
“…Note that single-site homogeneous olefin polymerization catalysis usually produces characteristic narrow molecular weight distributions with Đ ∼ 2.0. In some scenarios, broadened polyolefin Đs and multimodality can positively alter melt processing and polyolefin properties. …”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that bimodal PEs usually have the advantage of easier processing and altering tensile strength vs. monomodal HDPE type polymers. [61][62][63][64]…”
Section: Papermentioning
confidence: 99%
“…Consequently, CW can also be considered as a specific part of intermolecular chain transfers. However, its interest is due to the fact that it can lead to (hyper)branched/dendritic hydrocarbon polymers [24] that are tuned depending on the nature of the catalyst, [25,26,27,28,29] leading to stereospecific polymers, [28] or/with the complexity that the process involves the formation of radical species, [30] and this is also called radical ethene polymerization [31,32,33] . In addition, changing parameters such as monomer concentration or temperature can then block copolymerization [34,35,36,37,38,39] .…”
Section: Introductionmentioning
confidence: 99%
“…However, its interest is due to the fact that it can lead to (hyper)branched/dendritic hydrocarbon polymers [24] that are tuned depending on the nature of the catalyst, [25,26,27,28,29] leading to stereospecific polymers, [28] or/with the complexity that the process involves the formation of radical species, [30] and this is also called radical ethene polymerization. [31,32,33] In addition, changing parameters such as monomer concentration or temperature can then block copolymerization. [34,35,36,37,38,39] In the previous research on this topic, some remarkable properties were identified for the PAOs synthesized from the AlCl 3 /solvent system, however the mechanism of chain initiation, propagation and transfer was not clearly determined.…”
Section: Introductionmentioning
confidence: 99%